Effect of green tea catechins on the pharmacokinetics of digoxin in humans - Kim TE; Shin KH; Park JE; Kim MG; Yun YM; Choi DH; Kwon KJ; Lee J (Dove Medical Press, 2018)
Tae-Eun Kim,1 Kwang-Hee Shin,2 Jeong-Eun Park,2 Min-Gul Kim,3 Yeo-Min Yun,4 Dong-Hee Choi,5 Kyoung Ja Kwon,5 Jongmin Lee6 1Department of Clinical Pharmacology, Konkuk University Medical Center, Seoul, Republic of Korea; 2Department of Pharmacotherapy & Translational Research, College of Pharmacy, Research Institute of Pharmaceutical Sciences, Kyungpook National University, Daegu, Republic of Korea; 3Department of Pharmacology, Chonbuk National University Medical School, Jeonju, Jeonbuk, Republic of Korea; 4Department of Laboratory Medicine, Konkuk University Medical Center, Konkuk University School of Medicine, Seoul, Republic of Korea; 5Department of Medical Science, Konkuk University School of Medicine, Seoul, Republic of Korea; 6Department of Rehabilitation Medicine, Konkuk University School of Medicine, Seoul, Republic of Korea Background: Previous in vitro studies have reported the inhibitory effect of green tea on p-glycoprotein (p-gp) encoded by ABCB1. This study aimed to investigate the effect of green tea on the pharmacokinetics of digoxin, a typical probe drug of p-gp. Methods: Sixteen healthy volunteers participated in this study. At Day 1, 0.5 mg of digoxin was administered via oral route. After a 14-day washout period, 630 mg of green tea catechins (GTC) was administered via oral route, followed by 0.5 mg of digoxin 1 hour later. From Day 16 through Day 28, 630 mg of GTC was administered alone. At Day 29, 630 mg of GTC and 0.5 mg of digoxin were administered in the same way as Day 15. Blood samples for the pharmacokinetic assessments of digoxin were collected up to 8 hours after each dose. Pharmacokinetic parameters were estimated by noncompartmental analysis. Area under the curve (AUC) and peak plasma concentration (Cmax) were compared using mixed effect model between digoxin alone and digoxin with GTC. ABCB1 was genotyped to determine whether its polymorphism affects digoxin–GTC interaction. Results: Fifteen subjects completed the study. Compared to digoxin alone, the concomitant administration of digoxin and GTC significantly reduced the systemic exposure of digoxin: geometric mean ratios (GMR) and 90% confidence intervals (CI) of area under the concentration–time curve from time 0 to the last measurable time (AUClast) and Cmax were 0.69 (0.62–0.75) and 0.72 (0.61–0.85), respectively. The concomitant administration of digoxin and GTC following pretreatment of GTC (Day 29) similarly reduced the AUClast (GMR [90% CI]: 0.67 [0.61–0.74]) and Cmax (GMR [90% CI]: 0.74 [0.63–0.87]). In the comparison of the percentage changes from Day 1 (digoxin single administration) of AUClast between genotypes, C1236T variant type showed a significant difference to wild-type on Day 15 (concomitant administration of digoxin and GTC) (P=0.005). Conclusion: This study demonstrates that the coadministration of GTC reduces the systemic exposure of digoxin regardless of pretreatment of GTC. Keywords: digoxin, green tea, catechin, p-glycoprotein, pharmacokinetics, drug interaction